Effect of optical property of surfactant-treated TiO 2 nanostructure on the performance of TiO 2 photo-electrochemical cell - Rahman M.Y.A.; Umar A.A.; Roza L.; Salleh M.M. (2023)
TiO 2 nanostructures have been treated using different kind of surfactant to modify its optical absorption and morphology. TiO 2 nanostructures were prepared via simple method on indium tin oxide (ITO) surface, namely, liquidphase deposition technique (LPD) at 50C. The TiO 2 nanostructures film with a thickness of about 236 nm was annealed at 400C for 1 h in the air to enhance the interconnectivity of the particles. The dense and compact TiO 2 nanoparticle with different shape, particle size and surface morphology was used as a photovoltaic material in a photo-electrochemical cell of ITO/TiO 2/electrolyte/platinum. TiO 2 nanostructure films were treated with three different kinds of surfactants: cetyltrimethylammonium bromide (CTAB), hexamethylenetetramine (HMT) and polyvinylpyrrolidone (PVP). It was found that the film treated with HMT performed best, with a J sc of 57.5 ?A/cm 2. In conclusion, optical absorption, band gap and grain size of TiO 2 nanostructure influenced the performance of the cell.